Clinical features and natural history of RASopathy-associated hypertrophic cardiomyopathy in children. (14th October 2021) - Boleti, O; Field, E; Norrish, G; Dady, K; Summers, K; Lord, E; Smyth, S; Thompson, E; Cervi, E; Kaski, J P
Abstract: Background: The RASopathies are a group of genetic disorders caused by germline mutations in genes encoding components of the RAS/MAPK signalling pathway and frequently associated with hypertrophic cardiomyopathy (HCM). The clinical features and outcomes of RASopathy-related HCM are incompletely understood and most published studies are limited by relatively small numbers and incomplete clinical characterisation. Purpose: To describe the clinical features outcomes in a large, single-centre cohort of patients with RASopathy-associated HCM diagnosed <18 years. Methods: Data from 105 patients [68 (64.8%) males] diagnosed in childhood with RASopathy-associated HCM at a single specialist centre between 1985 and 2020 were retrospectively analysed. Results: The RASopathy diagnosis was Noonan syndrome in 69 patients (65.7%); NSML in 10 (9.5%); CFC in 6 (5.7%); Costello in 5 (4.8%) and 15 patients (14.2%) had another Noonan-like variant. 72 patients (68.6%) had a pathogenic/likely pathogenic variant in a RAS-MAPK gene, most commonly PTPN11 [n=25 (34.7%)], followed by RAF 1 [n=13 (18.1%)]. 100 patients (95.2%) were probands, 9 (8.6%) had family history of cardiomyopathy and 2 (1.9%) family history of sudden cardiac death (SCD). 52 (49.5%) had concomitant congenital heart defects (CHD) [ASD 13 (25%), VSD 6 (11.5%), PDA 1 (1.9%), >1 CHD 32 (61.5%)]. 29 (27.6%) had symptoms at baseline assessment and 56 (53.3%) were on cardiac medication. The distribution of left ventricular hypertrophy (LVH) was concentric in 47 (44.7%); 32 (30.5%) had asymmetric septal hypertrophy (ASH), and undocumented in 25 patients (23.8%). 45 patients (42.9%) had biventricular hypertrophy (BVH). Resting left ventricular outflow tract obstruction (LVOTO) was present in 39 (37.1%) with haemodynamically significant LVOTO (≥50mmHg) in 23 (21.9%). Resting right ventricular outflow tract obstruction (RVOTO) was present in 21 (20%). Over a median follow up time of 6 years, 19 patients (18.1%) died [1 (5.3%) SCD; 2 (10.5%) due to Heart Failure-related death; 1 (5.3%) due to another CVS cause; 5 (26.3%) due to a non-CVS cause and for 10 (52.6%) cause of death was unknown]. Incidence rate of death was calculated at 2.7 deaths per 100 person-years. Surgical septal myectomy was performed in 9 patients (8.6%) and 3 (2.9%) underwent cardiac transplantation. 14 patients (13.3%) suffered arrhythmic events [atrial tachycardia 6 (42.9%), Non-Sustained Ventricular Tachycardia 4 (3.8%), and Ventricular Tachycardia/Ventricular Fibrillation 4 (3.8%)]. Conclusion: To our knowledge, this is the largest cohort of RASopathy-associated HCM. The findings show a heterogeneous clinical presentation with a high prevalence of morbidity and mortality. Further work is needed to determine predictors of outcome in this population. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Onassis Foundation